A critical evaluation of mobile guided tour apps: Motivators and inhibitors for tour guides and customers. (October 2022) - Podsukhina, Ekaterina; Smith, Melanie Kay; Pinke-Sziva, Ivett
This paper identifies the motivators and inhibitors for using mobile tour guiding apps from the perspective of tour guides and customers. The study provides insights into the challenges of designing and developing apps through the evaluation of an existing tour guiding app and makes recommendations for further improvement. In-depth interviews were undertaken with tour guides from the WeGoTrip App as well as a sample of their customers. This study has important implications for app designers in terms of usability of such apps. It provides insights into the readiness of guides to adopt and promote such new developments, as well as the experiences of potential customers. The paper contributes to technology acceptance literature in the under-researched area of mobile app technology acceptance. The focus is on the motivators/inhibitors of guides and tourists to use/re-use mobile apps in the context of guided tours.